Hermeneutic Sociology of Knowledge for Intercultural Understanding - Norbert Schröer (Forum: Qualitative Social Research, 2009)
Intercultural communication is a form of interaction that is highly susceptible to errors. Hence, for a long time it has been studied primarily with regard to the kinds of misunderstandings that it typically produces. However, under pressure from increasing globalization, which also encompasses communication processes, questions concerning the limitations and possibilities for intercultural understanding are gaining the attention of scholars. This contribution addresses first the fundamental possibility of intercultural communication, and on this basis derives conclusions concerning how processes of intercultural understanding can be reconstructed. Finally, the attainable results and methods of a methodologically controlled reconstruction of these processes are described from the perspective of hermeneutic sociology of knowledge. URN: urn:nbn:de:0114-fqs0901408